Control System and Task Environment Effects on Ethical Judgment: An Exploratory Study of Industrial Salespeople - Robertson, Diana C.; Anderson, Erin (Organization Science, 1993)
The objective of this research was to determine the effects of a firm's control system and dimensions of the work task environment upon ethical judgments made by salespeople. Industrial field salespeople are likely to encounter ethical conflicts on a daily basis in their dealings with customers, competitors, and their own management. How they resolve such conflicts is believed to be a function of both individual characteristics and factors in the situation. This study focuses on situational factors in the form of organization design variables, particularly control system and task environment. The firm's control system includes its method of monitoring, supervising and compensating salespeople. The study develops fourteen ethics-related selling scenarios and assesses, via projective questioning, how 446 salespeople would react to them. Findings indicate that organization design does influence the behavior a salesperson considers appropriate to cope with ethical conflicts. In particular, salespeople operating under a more bureaucratic, input-based control system advocate more ethical behavior than do salespeople operating under a more output-based, laissez-faire control system. Also, salespeople who perceive the market to be competitive recommend less ethical behavior. However, the proportion of salary versus commission in the salesperson's compensation system does not have an effect on response. Differences are also discovered with respect to the salesperson's seniority, rank, and certain features of the task environment.